The US Navy enterprise resource planning architecture. (5th January 2005) - Gulledge, Thomas R.; Sommer, Rainer A.; Simon, Georg
This paper presents the design of the US Navy's enterprise resource planning (ERP) architecture, which takes the as-configured baseline across multiple ERP projects, and transforms it into a converged to-be integrated solution. The result is an architecture-based instance consolidation that is unique; for the Navy solution is the first architecture-driven instance consolidation.